Switching domain wall motion on and off using a gate voltage for domain wall transistor applications - Ma, Chuang (2019)
Spintronic devices such as magnetic random access memory and domain wall (DW) memory are attracting significant attention. Spin-field effect transistor devices have been proposed and researched for logic applications. In domain wall memory, the information is stored in magnetic domain states, which can be moved with a current above a certain threshold value. So far, the domain wall motion is only determined by the current density for most of the DW devices. Here, we demonstrate experimentally that a significant change in domain wall mobility can be achieved by applying a gate voltage. By applying a positive gate voltage, we show that the threshold current density for DW motion can be reduced by more than 10%. By choosing a suitable operating current, the domain wall motion can be switched on or off by the use of a gate voltage. These results are promising for designing high performance domain wall based transistor devices with faster operation speed and lower power consumption.